Digital disruption of the AEC industry: technology-oriented scenarios for possible future development paths - Lavikka, Rita; Kallio, Johanna; Casey, Thomas; Airaksinen, Miimu (Construction management and economics, 2018)
Decision-makers in the architecture, engineering and construction (AEC) industry lack knowledge about the implementation of digitalization to generate value. We applied a scenario planning method developed by Schoemaker and Mavaddat to provide decision-makers with information for using digital data and technologies to create value for customers. We aim to theoretically understand how the scenario planning process helps AEC decision-makers to make sense of the future. Our findings show that boundary spanners are needed for steering the discussions among industry actors towards shared knowledge about the technological, social, economic and political changes needed at the industry level to optimize the benefits of digitalization. Our findings also show that boundary spanners apply scenario figures as boundary objects to cross knowledge boundaries. Based on our findings, we theoretically conceptualize scenario planning as a boundary-spanning activity that enables AEC decision-makers from different fields to share tacit knowledge and to cross knowledge boundaries. The practical implication is that scenario planning provides a method for AEC decision-makers to make sense of the changes needed to realize the preferred future for the industry.